Covid-19 Impact on Supply Chains - Pandya, Poorva (2020)
Poorva Pandya POLICY SEMINAR Virtual Event - COVID-19, global markets and African agricultural trade: Impacts on growth and food security Organized by IFPRI, with support from the United States Agency for International Development (USAID) SEP 17, 2020 - 09:30 AM TO 11:00 AM EDT